2015
DOI: 10.1007/s12328-015-0585-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided drainage of an amoebic liver abscess extending into the hepatic subcapsular space

Abstract: Here, we report a case of an amoebic liver abscess (ALA) successfully treated with endoscopic ultrasound (EUS)-guided liver abscess drainage (EUS-LAD). A 37-year-old male with a liver abscess was referred to our hospital due to disease progression despite receiving antibiotic therapy. Computed tomography showed an intrahepatic abscess extending into the hepatic subcapsular space. The abscess could not be punctured through the hepatic parenchyma percutaneously due to the presence of hepatic subcapsular lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Placement of a 7F NCD alone was successful in draining large abscess (11 × 7 cm) as reported by Seewald et al [1]. Koizumi et al [6] and Yamamoto et al [9] reported success with a 5F NCD. A 10F NCD was used in Cases 2 and 3, as it is equivalent to a standard PCD catheter and allows thick contents to drain.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Placement of a 7F NCD alone was successful in draining large abscess (11 × 7 cm) as reported by Seewald et al [1]. Koizumi et al [6] and Yamamoto et al [9] reported success with a 5F NCD. A 10F NCD was used in Cases 2 and 3, as it is equivalent to a standard PCD catheter and allows thick contents to drain.…”
Section: Discussionsupporting
confidence: 59%
“…However, there is no uniformity in the literature regarding the choice of endoprothesis for transluminal drainage. Double pigtail stents 7F to 10F and/or 5F to 7F NCD were used as endoprostheses in the early reported cases [1][2][3][4][5][6]9]. In all recent publications, the authors have favored fully-covered self-expandable metal stent (FCSEMS) over plastic stents to achieve complete drainage and early abscess resolution [7][8]10].…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that EUS-guided drainage is an effective alternative to PD with some advantages, such as clear visualization, low risk of transcutaneous infection and the possibility of achieving direct access via a transluminal route without an external tube. 20…”
Section: Discussionmentioning
confidence: 99%
“…4 Endoscopic US-guided liver abscess drainage has been described as an effective alternative to open surgery in cases where a hepatic abscess requiring drainage is not accessible percutaneously. 36 Laparoscopy is a minimally invasive option for the treatment of abscesses that cannot be managed medically. Three ports usually provide adequate visualization to deroof the abscess, drain the pus, and irrigate the abscess cavity or abdomen in the event of an extrahepatic collection.…”
Section: Drainage Proceduresmentioning
confidence: 99%